Philippine labor and the economy course guidebook and selected readings - Sibal, Jorge V. (Quezon City Central Book Supply, 2008)
"Dean Sibal wrote this Guidebook primarily for students, facilitators, tutors and learners in the course on "Labor and the Economy" at UP SOLAIR and in subjects on "Labor Economics" and "Personnel and Industrial Relations" in other schools both at the collegiate and graduate studies levels. It can be used in the traditional face-to-face mode of teaching and facilitating or using the mixed on-line mode."--Preface.
Foreword -- Preface and acknowledgment -- Curriculum vitae of Professor Jorge V. Sibal -- Theoretical underpinnings -- 1. Industrial relations and the social sciences -- 2. System approach in the study of IR -- 3. Industrial relations and the economic system -- 4. Industrial relations and economic development -- 5. Industrial relations environment -- 6. The entrepreneur and the development of science and technology -- 7. The entrepreneurs and the economy -- Economic policies and issues -- 8. Wages of labor -- 9. Incomes policy -- 10. Trade and investment theories and globalization -- 11. Trade and investment policies -- 12. Fiscal policy and taxation -- 13. Financial system and monetary policy -- 14. Money and banking -- 15. Non-bank financial institutions -- 16. Capital market and long-term financing -- 17. The Philippine labor situation -- 18. Issues and problems in the Philippine industrial relations system -- 19. Policy issues and challenges in the Philippine labor sector -- 20. Industrial culture and industrialization -- 21. Strengthening offshoring in the Philippines -- 22. Measuring the informal sector in the Philippines and the trends in Asia -- 23. Local government unit practices in labor protection in the informal sector -- 24. Globalization and changes in labor market policies and industrial relations practices -- 25. Appendixes of charts, figures and tables.
Keywords: Labor -- Philippines; Philippines -- Economic policy